Mechanism of WeChat’s Impact on Public Risk Perception During COVID-19 - Zhuang Y; Zhao T; Shao X (Dove Medical Press, 2021)
Yue Zhuang, Tiantian Zhao, Xuanrong Shao School of Safety Science and Emergency Management, Wuhan University of Technology, Wuhan City, Hubei Province, People's Republic of ChinaCorrespondence: Tiantian ZhaoSchool of Safety Science and Emergency Management, Wuhan University of Technology, 122 Luoshi Road, Wuhan City, Hubei Province, People's Republic of ChinaEmail ztt220@whut.edu.cnPurpose: Taking COVID-19 as an example, this paper explores the mechanism of WeChat's impact on risk information transmission in social media and builds a model of WeChat's impact on public risk perception based on risk communication.Methods: Research primarily utilised the questionnaire survey method to collect and analyse public attitudes towards COVID-19 to achieve the research goals. We checked the adequacy of measurements and tested the hypotheses with regression analysis based on 801 participants in China.Results: The results indicated that the levels of the public WeChat COVID-19 risk information attention and trust had a significant positive impact on the public's risk perception and willingness of pandemic prevention. The improved public risk perception of COVID-19 as a mediator enhanced the public pandemic prevention ability, which allowed WeChat to play a more effective role in major disaster emergency.Keywords: COVID-19, WeChat, public risk perception, pandemic prevention